Application Design Implementation Planning Preparation Overhaul Production Machinery At PT Semen Indonesia (PERSERO) Tbk - Dionisius Oktavian Andana Putra; Henry Bambang Setyawan; Nunuk Wahyuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
PT Semen Indonesia (Persero) Tbk has very many production machines. Then there is a need for maintenance by overhauling. In the Planning Preparation Overhaul process that is used today uses the Microsoft Excel application that causes incomplete information to be available about the calculation of the overall percentage amount and the progress of Spare Parts, Fabrication, and Man Power.Of the things PT Semen Indonesia (Persero) Tbk wants to implement a Planning Preparation Overhaul system on website-based Production Machines. In Planning Preparation systems can integrate between system users according to their individual needs, provide information about the Planning Preparation progress and automatically calculate the current progress percentage according to the input given.Based on the results of the planning preparation overhaul machine production system with the Department of ICT and Management Service Development Staff of PT Semen Indonesia (Persero) Tbk, the results can facilitate the calculation of the total percentage of input progress list preparation, and the detailed information contained in the progress list preparation, as well as recording electronic planning Preparation Overhaul history to minimize the risk of losing data in the Planning Preparation process.Keyword: Website, planning preparation, production machinery, overhauls.